Analisis Putusan TUN No. 07/G/2025/PTUN.MDN Tentang Pembatalan Sertifikat Hak Milik dan Ditinjau dalam Perspektif Fiqih Siyasah - Rindi Apriyani; Ramadani Ramadani (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
This study addresses legal issues surrounding the cancellation of Freehold Title (Sertifikat Hak Milik or SHM) No. 296, owned by Sarudin Purba, pursuant to the Decision of the Head of the North Sumatra Regional Office of the National Land Agency (BPN) No. 20/Pbt/BPN.12/XI/2024. This decision was subsequently challenged in the Medan Administrative Court (PTUN) under Case No. 07/G/2025/PTUN.MDN. The study aims to analyze the Plaintiff's legal position and arguments, the Defendant's legality and authority in issuing the cancellation decision, and the Medan Administrative Court's ruling from the perspective of Fiqh Siyasah (Islamic political jurisprudence). A normative legal research method was employed, examining relevant legislation, court rulings, and legal literature. Legal materials were analyzed qualitatively to gain an understanding of the issues at hand. The findings indicate that Sarudin Purba filed the lawsuit due to perceived harm resulting from the SHM cancellation and questioned the procedural validity of the decision. The Head of the North Sumatra BPN Regional Office defended the decision based on administrative authority and agrarian regulations. The Medan Administrative Court dismissed the lawsuit, ruling that the object of the dispute contained no legal defects. Viewed through the lens of Fiqh Siyasah, the dispute touches upon principles of justice (al-‘adl), trustworthiness (amanah), public interest (al-maslahah), the administration of justice (siyasah qadhaiyyah), and the protection of property (hifzh al-mal). The study underscores the importance of balancing administrative legality, the protection of public rights, and the value of justice in governance.